Two-Hour Tobacco Abstinence Has No Effect on Cognitive Control in Male Patients With Nicotine Dependence: An ERP Study - Xue, Yanling; Zhou, Hongliang; Jiang, Chenguang; Liu, Xiaohong; Zhou, Zhenhe; Wang, Jun (Frontiers in Psychiatry, 2020)
Understanding the influence of pure nicotine abstinence on cognitive control may be helpful in eliminating nicotine dependence (ND) and preventing smoking relapse. This study was to investigate the effects of 2-hour tobacco abstinence on cognitive control in patients with ND. Twenty-five patients with ND and twenty-five healthy controls (HCs) completed three-stimulus (novelty) auditory oddball paradigm event-related potential (ERP) P300 measurements at the normality state (time 1) and the abstinence state (time 2). HCs were measured with P300 twice with a 2-hour time interval. Carbon monoxide (CO) levels were compared in the ND group using paired-samples t tests. HAMD and HAMA scores were compared between the ND group and the HC group using one-way ANOVA. The mean amplitudes and the mean latencies of P3a and P3b were compared between the ND group and HC group using repeated ANOVA. Results showed that there were significant differences in CO levels between the abstinence state and the normality state in the ND group. There were no significant differences in HAMD and HAMA scores for the abstinence state in the ND group or the normality state in the ND group and the HC group. For P3a, P3b amplitude and P3a latency, the main effect for ND group was significant. For P3a, P3b amplitude and latency, the interaction effect for group (ND group vs. HC group) × time point (time 1 vs. time 2) was not significant, and the main effect for time point was not significant. It concluded that patients with ND present cognitive control deficits, and 2-hour tobacco abstinence has no effect on cognitive control deficits in male patients with ND. Our findings may be helpful in eliminating nicotine dependence and preventing smoking relapse.